PENGARUH DESTINATION IMAGE, FASILITAS WISATA, DAN PERCEIVED VALUE TERHADAP BEHAVIORAL INTENTIONS (Studi Pada Pengunjung Taman Wisata Kopeng) - Sabrina Rahma Cipta; Naili Farida (Jurnal Ilmu Administrasi Bisnis, 2018)
Kopeng Park is one of the natural tourism object Semarang who experienced an increase in tourist visits during the last five years, but the number of visitors experienced a fluctuating decline even in 2015 and 2016. The purpose of this study is to find out the influence of the Destination Image and Tourist Facilities to the Behavioral Intention the Perceived Value as an intervening variable study of Tourism Site in Kopeng Park. The type of research is explanatory research. Questionnaire were adopted for data collection is this study. The sample used is 100 respondent. The sampling technique are accidental sampling and purposive sampling. The technique analysis are validity and reabilitas test, correlation coefficient, coefficient of the determination, simple linear regression, multiple linear regression, and test of significance (one-tailed) with IBM SPSS 23.0. The results showed a positive effect of destination image and tourist facilities on the perceived value and perceived value has positive influence on behavioral intention.  Recommendations for the managers of tourism destinations to build a strategy to be able to create perception consumer and superior than to its competitors through the advantages of tourist facilities and destinations in Kopeng Tourism Park, so the tourist numbers can increas.